Implementation of Payment Gateway in the Mobile-Based Pawon Mbok`E Eating House Ordering System - Fajar Mahardika; Ratih; R. Bagus Bambang Sumantri (Politeknik Negeri Cilacap, 2024)
This paper discusses the implementation of a payment gateway in the mobile-based Pawon Mbok'E eating house ordering system. The integration of a payment gateway into mobile applications is crucial for facilitating secure and convenient transactions. Pawon Mbok'E aims to enhance customer satisfaction by enabling users to order food and make payments seamlessly through their mobile devices. Method research used is development system order mobile based with payment gateway integration. This implementation involves selecting an appropriate payment gateway, integrating it with the existing ordering system, ensuring security measures are in place, and testing for reliability and user-friendliness. The success of this implementation will provide Pawon Mbok'E customers with a streamlined ordering and payment process, thereby improving overall service efficiency and customer experience. Obtained testing reliability with amount respondents there are 65 as well percentage prove 100%, subject This show if 65 respondents That breast milk as well as No there is incoming respondents​ to type Excluded